Sorption characteristics of dried and roasted male coconut (Cocos nucifera Linn.) flowers - Villostas, Ma. Sarah Jane C.; Francisco, Ma. Leonora dL. (Quezon City College of Home Economics, University of the Philippines Diliman, 2014)
ABSTRACT Coffee is one of the most consumed drinks after water. However, coffee produced by the local sector is not enough to supply the demands of the domestic market. Numerous coffee substitutes abroad are made from wheat, barley, malt, chicory, fig and in the Philippines, rice and corn. The male Cocos nucifera (coconut)flowers from the Tagnanan Tall X Malayan Red Dwarf Hybrid were used as a coffee substitute due to its under-utilization in coconut breeding. The objective of this study was to construct the sorption isotherm curve of dried and roasted coconut flowers through static gravimetric method using proximate equilibrium cells (PECs). From the sorption isotherm curve, the product was categorized under the BET Type II isotherm, which means that it is moderately hygroscopic. Five sorption isotherm models: BET, Henderson, Smith, Oswin, and Bradley models were used to analyze their suitability for predicting moisture sorption behavior of dried and roasted coconut flowers. The Smith model was found to be the best fit, with the BET model to have a relatively good fit as well. The monolayer moisture content was calculated using the BET equation and was found to be 2.19 g H2O/100 g solids. recommended packaging materials for dried and roasted coconut coffee include LDPE, BOPP, metallized PET/LDPE, and glass jars. Micobiological analysis of the product revealed that it was safe and hygienically-prepared. The results of this study can be used to optimize the packaging parameters for the shelf life of dried and roasted coconut coffee.
Thesis (B.S. Food Technology)--University of the Philippines Diliman.
Keywords: Coconut -- Philippines; Coconut -- Processing; Coconut coffee